2009 IEEE Sensors 2009
DOI: 10.1109/icsens.2009.5398215
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia detection in the UV region using an optical fiber sensor

Abstract: This paper describes an optical fiber sensor for the monitoring of ammonia gas. An open path optical technique is used to analyze the absorption lines of ammonia within the ultra violet region. Experimental results describing the operation of the sensor are presented and are compared with theory. A comparison between a commercial sensor has been carried out and cross sensitivity testing with regard to oxygen and carbon dioxide gas is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…In our last report [4], it is proven that the absorption lines for ammonia measured are similar with theoretical result as shown in Fig. 4.…”
Section: Experimental Results and Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…In our last report [4], it is proven that the absorption lines for ammonia measured are similar with theoretical result as shown in Fig. 4.…”
Section: Experimental Results and Analysissupporting
confidence: 86%
“…It is also reported that agricultural sector is the third main contributor to the greenhouse gases emission as shown in Fig. 1 [4]. Hence, a gas detection system for the agricultural sector must be developed in order to monitor greenhouse gases and ammonia emission.…”
Section: Introductionmentioning
confidence: 97%
“…The peaks vary at different wavelength from 172 nm to 217 nm as shown in Figure 2. However the interference study for the ammonia gas with the greenhouse gases are restricted to 200-230 nm wavelength range as the amm onia sensor developed [2] is designed to detect amm onia gas within this wavelength range.…”
Section: Theorymentioning
confidence: 99%
“…An optical fibre sensor using an open path technique for ammonia detection and measurement had been developed and previously reported [2]. Therefore an interference study needs to be performed in order to test the reliability of the sensor to measure amm onia gas in the presence of the greenhouse gases.…”
Section: Introductionmentioning
confidence: 99%
“…Until now many kinds of these optical fiber sensors have been reported and developed. Also, the performance of optical fiber sensors has been verified in many different sensing targets such as gases, chemicals, enzymes, and DNAs [2][3][4][5][6]. However, the glass optical fiber sensors show several defects; they need complicated pre-processing steps, such as fiber surface treatment, binding receptor layer on the quartz fiber surface or loading the sensor into glass capillary tube and sealing.…”
Section: Introductionmentioning
confidence: 99%